Contralesional Sensorimotor Network Participates in Motor Functional Compensation in Glioma Patients - Fang, Shengyu; Li, Lianwang; Weng, Shimeng; Guo, Yuhao; Zhong, Zhang; Fan, Xing; Jiang, Tao; Wang, Yinyan (Frontiers in Oncology, 2022)
Background Some gliomas in sensorimotor areas induce motor deficits but some do not. Cortical destruction and reorganization contribute to this phenomenon, but detailed reasons remained unclear. This study investigated differences of functional connectivity and topological properties in the contralesional sensorimotor network (cSMN) between patients with motor deficit and those with normal motor functions. Methods We retrospectively reviewed 65 patients (32 male) between 2017 and 2020. Patients were divided into four groups based on tumor laterality and preoperative motor status (deficit or non-deficit). Thirty-three healthy controls (18 male) were enrolled after matching for sex, age, and educational status. Graph theoretical measurement was applied to reveal alterations of topological properties of the cSMN by analyzing resting-state fMRI. Results The results of patients with different hemispheric glioma were similarity. Clustering coefficient, local efficiency, transitivity, and vulnerability of the cSMN significantly increased in the non-deficit group and decreased in the deficit group, as compared to the healthy group (p < 0.05). Moreover, the nodes of the motor-related thalamus significantly increased nodal efficiency and nodal local efficiency in the non-deficit group and decreased in the deficit group compared with the healthy group (p < 0.05). Conclusions We posited the existence of two stages of alterations of preoperative motor status. In the compensatory stage, the cSMN sacrificed stability to acquire high efficiency and compensate for impaired motor functions. With glioma growing and motor function being totally damaged, the cSMN returned to a stable state and maintained healthy hemispheric motor functions with low efficiency.